Optical Channel Capacity Upgrade Based on Multiwavelength Conversion XGM Using Semiconductor Optical Amplifier for Access Networks - Mohammad Syuhaimi Ab-rahman; Abdul Hameed Almabrok Swedan (International Journal of Optics)
This paper demonstrates a 10 Gb/s one-to-two-wavelength conversion configuration based on cross-gain modulation for optical access networks using a single TW-SOA. The method is capable of converting a signal data of specific wavelength 1541 nm to certain wavelengths of CW’s laser 1554 nm and 1558 nm with 4 nm spacing. The pump power level was classified due to channel response. A result obtained was the best power level offering wavelength converter between −6 and 3 dBm. The conversion efficiency achievement provided an acceptable result for probe signals. The findings of Q-factor performance were investigated. The Q values were found to be more than 9 for point to point transmission and 20 km fiber configurations for the original and converted signal. The technique implemented at 20 km and the power of all channels were adequate to provide a splitting ratio of 1/64 for the launched pump power 3 dBm.